Circulating CD3+CD8+ T Lymphocytes as Indicators of Disease Status in Patients With Early Breast Cancer - Han‐Kun Chen; Yi‐Ling Chen; Wei‐Pang Chung; Zhu‐Jun Loh; Kuo‐Ting Lee; Hui‐Ping Hsu (Cancer Medicine)
Abstract Background Identifying breast cancer markers with superior sensitivity, cost‐effectiveness, and practicality is imperative. Circulating immune cells and plasma cytokines hold promise as potential breast cancer markers. Aims To search and validate subtype of circulating immune cells and plasma cytokines as biomarkers for breast cancer patients. Materials & Methods Using flow cytometry, we investigated circulating immune cell profiles in patients with breast cancer and healthy controls. To validate clinical observations, an orthotopic breast cancer model was established. Results We analyzed 19 healthy controls and 27 patients (22 testing group and 5 validation group) with breast cancer and revealed distinct populations, including CD3+CD4+ T lymphocytes, cytotoxic T lymphocytes (CTLs; CD3+CD8+), polymorphonuclear myeloid‐derived suppressor cells (PMN‐MDSCs), and monocytic (M)‐myeloid‐derived suppressive cells. Patients with breast cancer exhibited reduced CD3+CD4+ T lymphocyte, CD3+CD8+ CTL, and CD33+CD15− M‐MDSC levels compared with healthy controls. Diminished CD3+CD8+ CTL levels correlated with advanced cancer grade, extensive intraductal components, and positive lymphatic tumor emboli. Treatment effects included decreased T lymphocyte/PMN‐MDSC levels, contrasting with elevated circulating CD3+CD8+ cell levels posttreatment, subsequently declining upon recurrence in the validation group. Elevated plasma chemokine (C–C motif) ligand 2 (CCL2) levels distinguished patients with breast cancer from healthy controls. Our orthotopic model supported decreased circulating CD3+CD8+ CTL levels in cancer‐bearing mice, followed by a postresection increase. Discussion We found that circulating CD3+CD8+ CTL levels decreased in patients with breast cancer, increased after treatment, and decreased again upon recurrence. Conclusion Circulating CD3+CD8+ CTL emerged as promising prognostic biomarkers and therapeutic targets in breast cancer management.